Progression of Structural Damage in the Sacroiliac Joints in Patients With Early Axial Spondyloarthritis During Long‐Term Anti–Tumor Necrosis Factor Treatment: Six‐Year Results of Continuous Treatment With Etanercept. Issue 5 (7th March 2019) - Rios Rodriguez, Valeria; Hermann, Kay‐Geert; Weiß, Anja; Listing, Joachim; Haibel, Hildrun; Althoff, Christian; Proft, Fabian; Behmer, Olaf; Sieper, Joachim; Poddubnyy, Denis
Abstract : Objective: To evaluate radiographic progression in the sacroiliac (SI) joints and to identify its predictors during long‐term treatment (up to 6 years) with the tumor necrosis factor (TNF) inhibitor etanercept in patients with early axial spondyloarthritis (SpA). Methods: Patients with early axial SpA who were treated with etanercept for up to 6 years in the Etanercept versus Sulfasalazine in Early Axial Spondyloarthritis (ESTHER) trial were selected based on the availability of radiographs of the SI joints. Two readers who were blinded with regard to clinical data scored the radiographs according to the modified New York criteria (range 0–4 per SI joint). A sacroiliitis sum score (total range 0–8) was calculated as the mean of the scores of the 2 readers. Active and chronic inflammatory changes in the SI joints on magnetic resonance imaging (MRI) performed at baseline, year 2, and year 4 were assessed according to the Berlin MRI scoring system. Results: Of the 76 patients originally included in the study, 42 had radiographs of the SI joints available at baseline and at least 1 follow‐up time point (year 2, 4, or 6). The mean ± SD change in the sacroiliitis sum score was 0.13 ± 0.73, −0.27 ± 0.76, and −0.09 ± 0.68, in the time intervals baseline to year 2, year 2 to year 4, and year 4 to year 6, respectively. In the longitudinal mixed model analysis, elevated C‐reactive protein level (β = 0.58 [95% confidence interval 0.24, 0.91]) and MRI SI joint osteitis score (β = 0.06 [95% confidence interval 0.03, 0.10]) were independently associated with progression of the sacroiliitis sum score. Conclusion: Our findings indicate that long‐term anti‐TNF therapy decelerates the progression of structural damage in the SI joints. Elevated CRP level and presence of osteitis on MRI were independently associated with radiographic sacroiliitis progression.